A two-step strategy to deposit a hydroxyapatite coating on polydopamine-coated polymer fibers. (1st January 2023) - Li, Jiaxin; Li, Ting-Ting; Zhang, Ying; Shiu, Bing-Chiuan; Lin, Jia-Horng; Lou, Ching-Wen; Liu, Liyan
Abstract: As the main inorganic component of human bones and teeth, hydroxyapatite (HA), with excellent bioactivity and biocompatibility, shows great potential in the bone tissue engineering field. Marine mussel-inspired polydopamine (PDA) possesses unique functional groups and thus can absorb the calcium ions from extracellular fluid, thereby triggering the precipitation of HA. This study is based on a two-step strategy. Using the chemical activity of PDA, polyvinyl alcohol/polylactic acid (PVA/PLA) braids were coated with a PDA layer that served as a template for the electrochemical deposition of a HA layer. The test results indicate that the resulting HA crystals were assembled on the polymer fibers in an urchin-like mannerwith a stratified structure. Subsequently, the HA/PDA-PVA/PLA braided bone scaffolds were immersed in simulated body fluid for ten days, after which the bone scaffolds were found to be completely coated with HA, indicating a good biomineralization capability. Cell activity of HA/PDA-PVA/PLA scaffolded by dopamine-assisted electrodeposition was 178.8% than that of PVA/PLA braids. This HA coating layer inspired by biochemical strategies may be useful in the field of bone tissue engineering.